Earnings Management: An Analysis of Corporate Strategy, Financial Performance, and Audit Quality - Wahyuni, Sri; Handayani, Erna; Pujiharto (Asian Economic and Financial Review, 2022)
This study aims to examine the effect of corporate strategy on earnings management with financial performance and audit quality as moderating variables. This study adopts the concept proposed by Miles and Snow in determining company strategy. The proxies for business strategy are the number of employees to total sales (EMPSAL), the capital expenditure ratio to total assets (CAPTA), and the dividend payout ratio (DPR). Financial performance is proxied by return on assets (ROA), auditor size measures audit quality, and discretionary accruals measure earnings management. The sample was determined using a purposive sampling method, and a sample of 16 companies was obtained with 80 observations. Companies grouped by prospector and defender strategies were analyzed using cluster analysis. Data analysis was carried out using moderated regression analysis (MRA). The results shows that a company's strategy affects earnings management, and that firm performance and auditor quality can moderate the relationship between corporate strategy and earnings management.